Condition Assessment of Concrete Elements through Two Nondestructive Ultrasonic Techniques - Rodríguez Roblero, María José (University of Waterloo, 2017)
Reinforced concrete is one of the materials most used in civil infrastructure, and the expected service life is generally for several decades. However, as any other material, concrete performance is affected by environmental conditions, the normal use of the structure, ageing and extreme load events. All of these factors affect the elements performance and can induce damage. Since all infrastructure components deteriorate over time, it is needed to assess their actual condition. Moreover, to implement adequate corrective measures it is needed to first detect damage and quantify its extent. There are different methods that may be used to inspect concrete elements, and the selection of the adequate technique depends on the property of interest and the available resources. Among the available inspection methods, the nondestructive techniques (NDT) are those used to detect defects, to estimate the material properties or to assess the integrity of components that do not affect the elements under evaluation. Every inspection technique has advantages and disadvantages; and consequently, the current trend is to use a combination of methods. Even though several nondestructive methods are commercially available, currently there is no comprehensive method to evaluate concrete columns. Taking in consideration these aspects, the main objective of this research was to develop a new nondestructive methodology and testing device that would allow inspecting concrete columns in a fast and reliable manner, without affecting their future performance. The proposed methodology relies on ultrasonic tests. The condition evaluation is based on measurements of wave velocity and wave attenuation because it is known that the attenuation is more sensitive to damage than the velocity. However, wave attenuation is generally not used in site evaluations because is very difficult to ensure consistent measurements in the field. To overcome this limitation, a new ultrasonic testing device was developed and tested. To verify the applicability of the methodology, reinforced and unreinforced concrete samples were tested in the laboratory, and a sample of in-service reinforced concrete columns was also evaluated. The main contributions of the research presented in this thesis are:  The construction of a new ultrasonic field testing device to test structural elements with circular cross section.  The evaluation of a new methodology to evaluate concrete elements based on statistical indexes computed from wave velocity and wave attenuation by testing a sample of in-service columns.  The new methodology allows detecting damage at earlier stages which would allow implementing opportune corrective measures.  The proposal and evaluation of an alternative testing procedure to evaluate freeze/thaw damage in concrete specimens based on wave attenuation measurements.  The appraisal of a new procedure to monitor progressive damage in concrete elements using surface wave measurements.  The evaluation of alternative signal processing techniques of the signals obtained from the surface wave testing to facilitate the analysis of the results.
Keywords: Reinforced concrete; Nondestructive testing (NDT); ultrasonic testing